USE OF ROLE PLAYING TECHNIQUES IN DRAMA LEARNING AS EFFORTS TO IMPROVE SPEAKING ABILITY IN INDONESIAN LANGUAGE LESSONS - Suryamah, Mamah; Chandraeni, Eni; Altaftazani, Deden Herdiana (IKIP Siliwangi, 2018)
Teacher and student interaction in the teaching and learning process does not have to be dominated by the teacher, but must rely on students. In determining learning techniques the teacher must pay attention to the involvement of students in learning. Speaking is the ability to speak articulation sounds or words to express, express and convey thoughts, ideas, and feelings. This study aims to determine the ability of students in speaking through the activities of playing drama characters, knowing the difficulties faced by students, and finding solutions to overcome student learning difficulties. The method used in this research is class action method. The research instrument consisted of observation, ability to speak practice, questionnaire and field notes. From the results of research and data processing, it was concluded that overall, the implementation of role playing learning techniques in improving speaking skills was carried out through three cycles of action implementation which focused on three pronunciation indicators, intonation, expression, had a considerable impact with the target of increasing speaking ability student. In other words, that speaking learning using role playing learning techniques has a positive impact on improving the ability of sixth grade students of Public Elementary School 055 Jatihandap, Bandung City.